COMPETITIVENESS - KEY ISSUES OF THE ROMANIAN ECONOMY - Gabriela-Liliana, CIOBAN (Strategii Manageriale)
Based on the theory that competitiveness plays an increasingly powerful role in creating prosperity, wealth, a large number of economists, researchers, scientists, highlight a number of approaches aimed, on the one hand, on the analysis of competitiveness at national or regional level, and on the other hand, on the ability of local firms to achieve competitive products and to commercialize them in the extern markets. In this context we aim to analyze and develop strategies and methods to help identify competitive areas at a national level. This is necessary because in our opinion the competitiveness of a company and / or country is more than wealth itself; it means a systematic process of wealth creation, plus a social system in which most citizens have access to material wealth. We consider in this respect that a country cannot automatically be considered competitive only if it is rich in natural resources. In our view, a competitive country creates wealth through labor, talent and organization and thus it manages to have a productive and creative potential making it independent of material resources.